2010
DOI: 10.1051/fruits/20010003
|View full text |Cite
|
Sign up to set email alerts
|

Composition minérale et vitaminique des fruits de cinq espèces sous exploitées en Algérie :Celtis australisL., Crataegus azarolus L., Crataegus monogynaJacq., Elaeagnus angustifoliaL.etZizyphus lotusL.

Abstract: Mineral and vitamin composition of fruits of five underexploited species in Algeria: Celtis australis L., Crataegus azarolus L., Crataegus monogyna Jacq., Elaeagnus angustifolia L. and Zizyphus lotus L. Abstract-Introduction. Celtis australis L., Crataegus azarolus L., Crataegus monogyna Jacq., Angustifolia elaeagnus L. and Zizyphus lotus L. are unconventional fruit trees and shrubs, which are very common in Africa, especially in Algeria. Their fruits are traditionally used as sources of vitamins and minerals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
6
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 12 publications
4
17
6
2
Order By: Relevance
“…In the literature, there appears to be the single report for carotenoids of 7.5 μ g/g in hackberry fruit (Boudraa et al. ), which is higher in comparison to values for β ‐carotene determined in the present study.…”
Section: Resultscontrasting
confidence: 84%
“…In the literature, there appears to be the single report for carotenoids of 7.5 μ g/g in hackberry fruit (Boudraa et al. ), which is higher in comparison to values for β ‐carotene determined in the present study.…”
Section: Resultscontrasting
confidence: 84%
“…Boudraa et al [15] indicated that C. azarolus L. and C. monogyna Jacq. species are found in Algeria.…”
Section: Mediterranean Hawthorn Fruit (Crataegus) Speciesmentioning
confidence: 98%
“…The mineral analysis of Z. lotus fruit showed that calcium, magnesium, and potassium were the predominance compounds with 490.84, 397.91, and 134.99 mg/100 g, respectively, [55] (Table 6). Similar amounts for magnesium and calcium were found in Z. lotus pulp [19], while higher contents of these three minerals are present in Z. lotus seeds, with amounts ranging from 92.41 to 1349.06 mg/100 g [11, 19].…”
Section: Classification Of Natural Biomolecules Of Z Lotusmentioning
confidence: 99%